Agriculture and climate change: Reducing methane emissions from irrigated rice - Wassmann, Reiner; Hosen, Yasukazu; Sumfleth, Kay (International Food Policy Research Institute, 2009)
Rice is grown on more than 140 million hectares worldwide and is the most heavily consumed staple food on earth. Ninety percent of the world’s rice is produced and consumed in Asia, and 90 percent of rice land is—at least temporarily—flooded. The unique semiaquatic nature of the rice plant allows it to grow productively in places no other crop could exist, but it is also the reason for its emissions of the major greenhouse gas (GHG), methane. Methane emissions from rice fields are determined mainly by water regime and organic inputs, but they are also influenced by soil type, weather, tillage management, residues, fertilizers, and rice cultivar. Flooding of the soil is a prerequisite for sustained emissions of methane. Recent assessments of methane emissions from irrigated rice cultivation estimate global emissions for the year 2000 at a level corresponding to 625 million metric tons (mt) of carbon dioxide equivalent (CO2e). Midseason drainage (a common irrigation practice adopted in major rice growing regions of China and Japan) and intermittent irrigation (common in northwest India) greatly reduce methane emissions. Similarly, rice environments with an insecure supply of water, namely rainfed rice, have a lower emission potential than irrigated rice. Organic inputs stimulate methane emissions as long as fields remain flooded. Therefore, organic inputs should be applied to aerobic soil in an effort to reduce methane emission. In addition to management factors, methane emissions are also affected by soil parameters and climate.